Is the ADP ribose site of the Chikungunya virus NSP3 Macro domain a target for antiviral approaches? - Shimizu, Jacqueline Farinha [UNESP]; Silva Martins, Daniel Oliveira [UNESP]; McPhillie, Martin J.; Roberts, Grace C.; Zothner, Carsten; Merits, Andres; Harris, Mark; Gomes Jardim, Ana Carolina [UNESP] (Elsevier B.V., 2020)
Chikungunya virus (CHIKV) is a mosquito-transmitted virus of special concern as it causes Chikungunya fever, characterized by an acute febrile illness, rash, and arthralgia that can progress to chronic and debilitating arthritic symptoms. The effects of climate change on the geographic distribution of the mosquito vector has the potential to expose more of the globe to this virus. No antiviral agents or vaccines are currently available against CHIKV infection and the development of novel therapies that may lead to a future treatment is therefore necessary. In this context, the ADP-ribose binding site of the CHIKV nsP3 macro domain has been reported as a potential target for the development of antivirals. Mutations in the ADP-ribose binding site demonstrated decreased viral replication in cell culture and reduced virulence. In this study, 48,750 small molecules were screened in silico for their ability to bind to the ADP-ribose binding site of the CHIKV nsP3 macro domain. From this in silico analysis, 12 molecules were selected for in vitro analysis using a CHIKV subgenomic replicon in Huh-7 cells. Cell viability and CHIKV replication were evaluated and molecules C5 and C13 demonstrated 53 and 66% inhibition of CHIKV replication, respectively. By using a CHIKV-Dual luciferase replicon contain two reporter genes, we also demonstrated that the treatment with either compounds are probably interfering in the early replication rather than after RNA replication has occurred.
Keywords: Chikungunya virus; Antiviral; nsP3; Macro domain